QUALITY AND ITS PARAMETERS – A BASIC CRITERIUM FOR THE MOVEMENT OF THE MATERIAL FLOW IN THE LOGISTICS PROCESS: QUALITY AND ITS PARAMETERS – A BASIC CRITERIUM FOR THE MOVEMENT OF THE MATERIAL FLOW IN THE LOGISTICS PROCESS - Ognyanov , Vasko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The aim of the paper is to present theoretical principles and practical recommendations for management of the logistics system and the parameters of material flows quality. The main approach for research of this problem is a set of scientific knowledge and special methods which allow the identification of the basic trends and characteristics for control of the quality parameters of the material flows. The paper presents the idea for the creation of a system to control the material flows quality in the logistics systems in order to optimize the general expenses and quality improvement.